A review and comparison of the indoor air quality requirements in selected building standards and certifications. (December 2022) - Wei, Guanqiong; Yu, Xiyang; Fang, Lin; Wang, Qingqin; Tanaka, Toshio; Amano, Kenji; Yang, Xudong
Abstract: Indoor air quality (IAQ) indicators have been set by various building standards and certifications to evaluate indoor environments. The goal of this study is to review and compare IAQ requirements, including indoor air pollutant types and concentration limitations. 26 standards and certifications developed by governments, non-profit organizations, and associations were selected from six countries and an international organization. The standards and certifications were classified into basic, green, and health levels depending on their positioning and content. The basic level was the bottom line for indoor air hygiene, the green level expected to improve IAQ but with a greater focus on energy and sustainability, and the health level's primary target was to promote occupant health and well-being. IAQ indicators, including pollutant types and concentration limits, were compared in regards to organic compounds, inorganic compounds, particulate matter, and others at the overall, same, and different levels. Formaldehyde, benzene, carbon dioxide, particulate matter, and radon were the pollutants mostly considered by all three levels of standards and certifications. For many organic pollutants and particulate matter, Chinese standards are progressively stricter from basic to health level. This however is not always true for other standards. For inorganic pollutants, the latter two levels were usually not more stringent than the basic level. Currently, even health-level standards still do not consider the IAQ requirements related to epidemic prevention. Based on the target and positioning of the health-level standard, IAQ requirements may continue to improve in the future and enhance the consideration of epidemic prevention. Highlights: 26 worldwide building standards and certifications related to IAQ were reviewed and compared. IAQ indicators in building standards were classified into basic, green, health levels. The three levels are progressive in their targets and positioning in regards to the IAQ. Pollutant concentration limits are not set under same comparable conditions. Epidemic prevention should be further considered in future standards.